Characterization of Shiga toxin-producing Escherichia coli O130:H11 and O178:H19 isolated from dairy cows - Fernández, Daniel; Krüger, Alejandra; Polifroni, Rosana; Bustamante, Ana; Sanso, Andrea M.; Etcheverría, Analía I.; Lucchesi, Paula M.; Parma, Alberto E.; Padola, Nora Lía (Frontiers in Cellular and Infection Microbiology, 2013)
Shiga toxin-producing E. coli (STEC) are isolated from human patients with bloody diarrhea, hemorrhagic colitis (HC), and hemolytic uremic syndrome (HUS). In the last years, the infections with non-O157 serotypes are increasing their frequency of association with human disease. STEC produce Shiga toxin (Stx) and other virulence factors that could contribute to human pathogenesis. Cattle are the main reservoir and the transmission to humans is through the consumption of undercooked meat, non-pasteurized dairy products, and vegetables or water contaminated with feces. We have previously determined that O130:H11 and O178:H19 serotypes were the most prevalent in dairy cows from Argentina. In the present study, 37 and 25 STEC isolates from dairy cows belonging to O130:H11 and O178:H19 serotypes, respectively, were characterized regarding to their cytotoxicity on Vero cells, stx subtypes, presence of sab and typing by multiple-locus variable-number tandem repeat analysis (MLVA). All strains demonstrated a cytotoxic effect, and in O130:H11 isolates, stx2EDL933 was the predominant subtype. In O178:H19 isolates the main stx2 subtype was stx2vha. The sab gene was detected in 65 and 24% of the isolates belonging to O130:H11 and O178:H19, respectively. Only one MLVA profile was identified among the O130:H11 isolates meanwhile 10 MLVA profiles were detected among the O178:H19 isolates which were grouped in two main clusters. In conclusion, our data show that O130:H11 and O178:H19 STEC isolates encode virulence factors associated with severe human disease and both serotypes should be considered for routinely testing. Our subtyping experiments showed that isolates could be distinguished based on the stx2 subtype and the presence/absence of sab gene, and for isolates belonging to O178:H19, also when the MLVA type was considered. However, MLVA subtyping of O130:H11 isolates will require the development of more specific markers.